Peningkatan Keterampilan Bertanya Siswa melalui Pendekatan Problem-Solving - Sefni Rama Putri; Ilham Khairi Siregar (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2026)
This study aims to describe the difference in the improvement of students' questioning skills between the group that participated in content mastery services using a problem-solving approach and the group that participated in content mastery services using the lecture method. The research used a quantitative approach with a quasi-experimental research type and a non-equivalent pretest-posttest control group design. The research subjects consisted of 40 students from the Department of Guidance and Counseling at Universitas Negeri Gorontalo, consisting of 20 students in the experimental group and 20 students in the control group. Subjects were selected using a purposive sampling technique based on predetermined questioning skill criteria. Data were collected using a questioning skills questionnaire with a four-choice Likert scale. The experimental group received content mastery services using a problem-solving approach, while the control group received content mastery services using the lecture method. The results of the descriptive analysis showed that after treatment, 45% of students in the experimental group were in the very skilled category, 50% were in the skilled category, and 5% were in the moderately skilled category. In the control group, 60% of students were in the skilled category and 40% were in the moderately skilled category. No students in the control group reached the very skilled category. Thus, descriptively, content mastery services using a problem-solving approach show better results than the lecture method in improving students' questioning skills.